Program evaluation of an english language teacher education practicum: insights from supervisors, student teachers, and graduates - Celen, Kıymet Merve. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2016., 2016)
This study aims to evaluate the practicum program offered at the Foreign Language Education Department (FLED) at an English-medium state university in Turkey to discover (1) the extent to which the Ministry of National Education (MoNE) English language teacher competencies were achieved, (2) its strengths and weaknesses, and (3) the reported needs and possible solutions. Participants of the study were university supervisors, student teachers, and program graduates. Data came from student teacher and program graduate surveys, focus group interviews with student teachers, and individual interviews with university supervisors. For MoNE competencies, the results pointed to an improvement for a better understanding and more use of assessment and evaluation in the classroom and use of activities appropriate for learners with special needs. Higher ratings were elicited for teaching practices and understanding oneself as a professional. Knowledge, skills, dispositions, field experiences and student teaching internship, and quality of instruction were found to be the strengths of the practicum experience in contrast to learner diversity and technology components of the teacher education program. Strengths of the program included experiences in classrooms at various grade levels, seminar discussions and peer feedback, good relationships with cooperating teachers, and involvement and guidance by university supervisors while suggestions pointed to an earlier or more practice or observation, different school contexts, cooperation with cooperating teachers, and improvement in assessment, observations, and technology use.
Keywords: Language teachers -- Training of.; Language and languages -- Study and teaching.